Exploring and analysing the notion of worst case scenario in professional rugby union - Haakma, M. L. (University of Waikato, Hamilton, 2021)
Rugby union is an interval-based contact sport, demanding intermittent bursts of high-intensity running, collisions and impacts. Players need to be conditioned in a way that best prepares them for the demands of the game, and to perform repeated bouts of high-intensity workloads. Understanding the peak periods of `play` and the `worst case scenario` (WCS) in rugby union is essential to inform effective training interventions. Through a review of current literature around the notion of WCS and peak periods of play, limitations in existing research methods were identified. Specifically, limitations within the ability of global positioning system (GPS) units to quantify contact and collision workloads, and the error of data recorded over short distances and durations. Limitations within the methodology of fixed-time epochs and rolling-average epochs as a way of quantifying WCS were also explored. After reviewing the current literature, this thesis encloses an original and innovative study. This research aims to determine a potentially more accurate representation of WCS by quantifying the maximal intensity locomotive demands during `ball in play` (BIP) for a single play, and across a series of consecutive plays through an innovative rolling-MultiPlay epoch analysis (5 min, 10 min, 15 min, 20 min epochs). This study will also give a contextual indication by identifying the segment of the game in which these maximal workload demands occur. Data was collected for 51 professional rugby union players over the 2019-2020 seasons. All players wore GPS units (Apex Pro Pod, STATSport, Newry, NIR). All games were filmed and coded through the Sportscode software (Sportscode V8.9, Sportstec, Australia) which was then combined with GPS data from which drills were created for each BIP period. This data was then analysed through a bespoke software where the maximum BIP (MaxBIP) values for a range of GPS metrics were determined for each positional subgroup. A WCS BIP analysis was completed as well as a WCS MultiPlay analysis. Each half of the game was divided into 4 equal segments, and the segments where the MaxBIP values occurred were identified. Practical applications for indicative training drills for WCS BIP, WCS 5 minute drill, and WCS 20 minute drill are provided. In conclusion, there were no distinct patterns found within the data that suggests the WCS MaxBIP demand could occur in any segment of the game. Therefore, we believe it would be beneficial for players to be conditioned for these peak demands to occur at any stage of the game.